Privacy Concerns Versus Personalized Health Content—Pregnant Individuals’ Willingness to Share Personal Health Information on Social Media: Survey Study - Haijing Hao; Yang W Lee; Marianne Sharko; Qilu Li; Yiye Zhang (JMIR Formative Research)
Abstract BackgroundOften lacking immediate access to care providers, pregnant individuals frequently turn to web-based sources for information to address their evolving physical and mental health needs. Social media has gained increasing prominence as a source of news and information despite privacy concerns and unique risks posed to the pregnant population. ObjectivesThis study investigated the extent to which patients may be willing to disclose personal health information to social media companies in exchange for more personalized health content. MethodsWe designed and deployed an electronic survey to pregnant individuals worldwide electronically in 2023. We used the classical Internet Users’ Information Privacy Concerns (IUIPC) model to examine how privacy concerns modulate pregnant individuals’ behaviors and beliefs regarding risk and trust when using social media for health purposes. Results were analyzed using partial least squares structural equation modeling. ResultsAmong 317 respondents who initiated the survey, 84% (265/317) of the respondents remained in the study, providing complete responses. Among them, 54.7% (145/265) indicated willingness to provide their personalized health information for receiving personalized health content via social media, while 26% (69/265) were uncertain and 19.3% (51/265) were opposed. Our estimated IUIPC model results are statistically significant and qualitatively align with the classic IUIPC model for the general population, which was previously found in an e-commerce context. The structural model revealed that privacy concerns (IUIPC) negatively affected trusting beliefs (β=−0.408; PPPPPR ConclusionsWe find that more than half of the pregnant individuals are open to sharing their personal health information to receive personalized content about health via social media, although they have more privacy concerns than the general population. This study emphasizes the need for policy regarding the protection of health data on social media for the pregnant population and beyond.